A banquet of consequences : a Lynley novel - George, Elizabeth (New York : Penguin Books, 2016)
As Inspector Thomas Lynley investigates the London angle of an ever more darkly disturbing case, his partner, Barbara Havers, is looking behind the peaceful façade of country life to discover a twisted world of desire, deceit, and murder. The suicide of William Goldacre is devastating to those left behind. But what was the cause of his tragedy and how far might the consequences reach? Is there a link between the young man's leap from a Dorset cliff and a horrific poisoning in Cambridge? After various career-threatening issues with her department, Barbara Havers is desperate to redeem herself. So when a past encounter with a bestselling feminist writer and her pushy personal assistant gives her a connection to the Cambridge murder, Barbara begs Thomas Lynley to let her pursue the crime.
Keywords: Murder -- Investigation -- Fiction; Detective and mystery fiction